Russian Federation : Financial Sector Stability Assessment Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents the Financial Sector Stability Assessment Update on the Russian Federation. Indicators of bank soundness and performance are broadly favorable but credit risk poses a challenge over the medium term, and capitalization should rise to support continued banking sector development. The system has weathered the global credit crunch that began in mid-2007, yet the funding model is coming under strain as the turmoil in global markets continues. Capital markets have grown dramatically in recent years but remain highly concentrated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet